2022
DOI: 10.1186/s12871-022-01866-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided bilateral modified-thoracoabdominal nerve block through a perichondrial approach (M-TAPA) in patients undergoing laparoscopic cholecystectomy: a randomized double-blind controlled trial

Abstract: Background Modified thoracoabdominal nerve block through the perichondrial approach (M-TAPA) is a new technique that provides effective analgesia of the anterior and lateral thoracoabdominal walls by administering local anesthesia only to the underside of the perichondral surface. The primary purpose of the present study was to investigate the postoperative analgesic efficacy of M-TAPA block performed before surgery in patients undergoing laparoscopic cholecystectomy (LC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Gungor et al, compared the M-TAPA block with LA infiltration after LC and reported that, in the M-TAPA group, postoperative pain and the need for rescue analgesia were significantly lower 21 . Bilge et al, showed that the M-TAPA block decreased pain and consumption of tramadol compared with the control group 22 . Erturk et al, compared the TAPA block with the M-TAPA block after LC and showed that NRS scores, tramadol consumption, and rescue analgesic use were similar in the postoperative period 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Gungor et al, compared the M-TAPA block with LA infiltration after LC and reported that, in the M-TAPA group, postoperative pain and the need for rescue analgesia were significantly lower 21 . Bilge et al, showed that the M-TAPA block decreased pain and consumption of tramadol compared with the control group 22 . Erturk et al, compared the TAPA block with the M-TAPA block after LC and showed that NRS scores, tramadol consumption, and rescue analgesic use were similar in the postoperative period 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The multiple‐injection technique and the oblique subcostal TAP block can provide broad‐spectrum analgesia but require multiple punctures or a longer needle 2,12,13 . In contrast, M‐TAPA is advantageous because it provides broad (Th7–11) analgesia with only a single injection of LA 5,8,14–17 …”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound‐guided procedure avoids penetration of the transversus abdominis muscle and peritoneum. Thus, M‐TAPA is a low‐risk technique and therefore, is an alternative analgesia technique for LC 8,17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations